2014
DOI: 10.1038/labinvest.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Ang-Tie2 and Dll4-Notch signaling has opposing effects on tumor endothelial cell proliferation, evidenced by a new flow cytometry method

Abstract: Sustained angiogenesis is essential for tumor growth as it provides the tumor with a network of blood vessels that supply both oxygen and essential nutrients. Limiting tumor-associated angiogenesis is a proven strategy for the treatment of human cancer. To date, the rapid detection and quantitation of tumor-associated endothelial cell (TAEC) proliferation has been challenging, largely due to the low frequency of endothelial cells (ECs) within the tumor microenvironment. In this report, we address this problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…[60][61][62][63] Increased DLL4/Notch expression in the large and mature vessels of gliomas promotes a quiescent vascular phenotype that reduces the density of the tumor vasculature. 61,[64][65][66] However, DLL4 in some cases is associated with high MVD and is expressed in some microvascular formations of gliomas, including delicate capillary-like, 67,68 garland-like, 68 sprouted and clustered 60,69 and glomeruloid cells. 62,68,69 These findings indicate a complex relationship between DLL4 and tumor angiogenesis.…”
Section: Delta-like Ligands In Gliomasmentioning
confidence: 99%
“…[60][61][62][63] Increased DLL4/Notch expression in the large and mature vessels of gliomas promotes a quiescent vascular phenotype that reduces the density of the tumor vasculature. 61,[64][65][66] However, DLL4 in some cases is associated with high MVD and is expressed in some microvascular formations of gliomas, including delicate capillary-like, 67,68 garland-like, 68 sprouted and clustered 60,69 and glomeruloid cells. 62,68,69 These findings indicate a complex relationship between DLL4 and tumor angiogenesis.…”
Section: Delta-like Ligands In Gliomasmentioning
confidence: 99%
“…However, other signalling pathways and effectors may be involved in this type of malignant disease and their discovery would uncover the possibility of novel therapies in the future. The currently available therapy options for GBM (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64) are summarised in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor angiogenesis is closely related to the occurrence, development and prognosis of a variety of tumors. Some researchers reported that vascular endothelial cells can be labeled by lots of factors, such as FSRA/WF, cluster of differentiation (CD)31, CD34, Tie2 and TEC‐11 and so on. The marker CD34 is characterized by high reproducibility and stability in the pan‐vascular endothelial cells that are commonly used for immunohistochemical identification of different tumors.…”
Section: Introductionmentioning
confidence: 99%